Padawan Municipal Council / Gabraline Andrew - Andrew, Gabraline (Universiti Teknologi MARA, Sarawak, 2019)
Padawan Municipal Council which is formerly known as Kuching Rural District was formed at the end of 1956 under the provisions of the Local Authority Ordinance 1948. The present location of Padawan Municipal Council (MPP) office is located at Kota Padawan, 10th Mile, Jalan Penrissen, Kuching. Padawan Municipal Council, it consist of ten departments which are the Chairman Office, Secretary Office, Management Services Division, Community Development, Tourism, Corporate and Public Relation Division, Finance Division, Health and Municipal Services Division, Valuation and Rating Division, Engineering Division, Planning and Development Division and Legal and Enforcement Division. Besides that, there are several sections under each division. Such as, the secretary office has one section under it which is the Legal Unit. The Management Services Division consist of three sections under it, which is Human Resource Section, General Admin Section and Transformation and Innovation Section. For the Finance Division it also consists three sections under it, which are Accounting, Expenditure Monitoring and Control Section, Financial Management Section and Revenue Collection Section. As for Health Municipal Services Division there are six sections under it, which are Market and Hawker Section, Food Quality Control and Health Licensing Section, Building Sanitation Section, Solid Waste Section, Liquid Waste Section and Maintenance Section.